Debunking the Myth of the Historic Supremacy of Annual Accounting for Income Taxes: A Coalescence of Non-Literal Interpretation with Original Intent Analysis - Myron C. Grauer (Washington University Law Quarterly, 1989)
As this Article's purpose is mainly to determine if historically Congress desired annual accounting to be tempered by some policies that conflict with those behind annual accounting, this Article will forego the use of economic and financial models in favor of an examination of the historical context in which the early annual accounting provisions developed in the statutory and regulatory scheme. The decision not to engage in economic and financial modeling in this Article is also justified by the fact that this Article will be evaluating whether courts engaged in a proper balancing of policy goals in an era before the legal literature contained today's economic and financial modeling. It is thus only fair to those courts to evaluate what they were doing in the context of the information available to them at that time.
Keywords: Income tax – Accounting